2015
DOI: 10.1111/1475-6773.12278
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Surgery Centers and Their Intended Effects on Outpatient Surgery

Abstract: The opening of an ASC in a Hospital Service Area resulted in a decline in hospital-based outpatient surgery without increasing mortality or admission. In markets where facilities opened, procedure growth at ASCs was greater than the decline in outpatient surgery use at their respective hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 20 publications
0
25
0
1
Order By: Relevance
“…The measure of quality in ambulatory surgery centres is, today, the focus of pressure from stakeholders. 22,23 Quality control is an essential and continuous feature of practice, in order to assess and improve care provided to patients. 22 Currently, there are no international guidelines on quality control for ambulatory surgery centres and international standard values for quality indicators are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measure of quality in ambulatory surgery centres is, today, the focus of pressure from stakeholders. 22,23 Quality control is an essential and continuous feature of practice, in order to assess and improve care provided to patients. 22 Currently, there are no international guidelines on quality control for ambulatory surgery centres and international standard values for quality indicators are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In order to identify, resolve and avoid problems in ambulatory surgery centres, it is essential to continuously control quality indicators, selecting those that are the most accurate. 18,22,23 The correct monitoring and interpretation of quality indicators in ambulatory surgery allows activities performed in ambulatory surgery centres to be assessed, showing progressive improvement in various indicators and demonstrating how to sustain continuous progress in the quality of these centres. 5,18 The purpose of this study is to review global quality indicators used in ambulatory surgery and to compare them with those used in Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…The ambulatory care is provided at private offices, independent surgery center, day surgery departments of the hospitals, private clinics, and the non-forprofit comprehensive health centers. It is reported that over 75% of the surgeries were performed in ambulatory care in 2010 (27,28).…”
Section: Health System and The Ambulatory Care Provisionmentioning
confidence: 99%
“… 2 As the demand for surgery outweighs many hospitals capacity to supply operative time, ambulatory surgery centers (ASCs) have increased by 60%, followed by an increased in outpatient surgeries in the Medicare population 40%. 3 , 4 Additionally, ASCs are able to perform the same procedure as a hospital at a lower cost by accepting a lower facility reimbursement fee. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%